The effect of work motivation and work discipline on the work achievement in the Camat Munte Office Karo District - Girsang, Elisabet (JURNAL GLOBAL MANAJEMEN; Vol 10 No 1 (2021): JUNIDO - 10.46930/global.v10i1.1127, 2021)
This study aims to determine the effect of motivation and work discipline on employee achievement at Kantor Camat Munte Kabupaten Karo. The number of samples in this study were 22 respondents who were Civil Servants at the Office of the Sub-District Head of Munte Karo Regency. Library research and field research were used in this research. Data were analyzed using multiple linear regression analysis, and hypothesis testing was performed using t test , F test and determination coefficient test. The results of the study obtained multiple regression equations Y=-0,20+1,990X ₁ -0,688X ₂ , which explains that the regression coefficients possessed by the variables of motivation and work discipline give a positive direction to the achievement of the employees of the Karo District Head Office. Based on hypothesis testing, it is found that motivation has a positive and significant effect on employee achievement, with a t count (7,040)> t table value (2.085), or a sig value (0.000) < alpha (0.05). Work discipline has a positive and significant effect on employee achievement, with a t count (-2,55) by the value of F count (39,026) > F table (3.49) and a significance of 0.000 <α=0.05. The coefficient of determination test results also showed that 80,4% of employee achievement variables could be explained by the variables of motivation and work discipline. While the remaining 19,6% is explained by other variables not examined in this study